Improvement of the liquid-jet sulfitators construction to increase the efficiency of sulfitation treatment of sugar production liquids - V. O. Gorodetsky; S. O. Semenikhin; N. I. Kotlyarevskaya; M. M. Usmanov (Новые технологии)
The article discusses and analyzes the construction of liquid-jet sulfitators used in the beet sugar industry. The importance of sulfitation treatment in the sugar beet processing and raw cane sugar technology is noted and the main advantages of its use at various technological stages are given, namely, preparation of extractant used for diffusion sucrose extraction out of beet cossettes, thin juice processing, thick juice with B- and C-remelts processing, as well as raw cane sugar remelt processing. The advantages and disadvantages of liquid-jet sulfitators in comparison with other constructions are noted and criteria for their improvement are given. It has been noted that the created ejection, which sucks in the sulphitation gas into the contacting chamber, and the fact that the absorption of sulfur dioxide occurs on a larger surface than in other types of structures the main advantages of liquid-jet sulphitators. The main disadvantages are the short length of the contacting chamber, which is insufficient for ensuring complete absorption of sulfur dioxide, as well as instability of the generated ejection when the productivity changes. This determines the criteria given in the article for the improvement of liquid-jet sulfitators. The description of the developed construction of the sulphitator centrifugal-jet nozzle of sugar production liquids is given, which provides: the stability of the sulphitation gas supply in a wide range of plant productivity; stability of the hydroaerodynamic regime of the system «treated liquid – sulphitation gas» inside the sulphitator; sufficient contact time for complete dissolution in the treated liquid of the sulfur anhydride contained in the sulphitation gas. The advantages of the developed centrifugal-jet sulfitators in comparison with typical liquid-jet sulfitators are noted: ensuring the operation range of 50-120% of the nominal capacity (plant production capacity); significant reduction in the technical sulfur consumption for the sulphur anhydride production, which is used as a reagent for the sulfitation treatment of liquids in beet sugar processing; reduction of harmful emissions into the atmosphere due to 100 % sulfur anhydride dissolution in the treated liquid.